Assessment of students’ feedback for online courses of Institute of Neo Education (iNED) / Dr Syerina Azlin Md Nasir, Dr Wan Fairos Wan Yaacob and Nurazleena Ismail - Md Nasir, Syerina Azlin; Wan Yaacob, Wan Fairos; Ismail, Nurazleena (2018)
Online learning has now become common in many higher educations. This tool has provided the flexibility, availability and cost effectiveness of teaching and learning for students at any time, from any place (Castle and McGuire, 2010). The advancement of technologies available at present allows a variety of online mechanisms and approaches developed to maintain the level of quality comparable to face-to-face (f2f) learning. However, the opportunity of online learning brings about consideration in assessment. Online continuous assessment is needed to ensure that effective learning will take place. Summative evaluation through surveys can be found in student assessment (Castle and McGuire, 2010) and peer assessment (Van der Pol et al., 2008) as tools to give effective online feedback about the quality of the courses taught, rather than simply rely on tests, quizzes and grades. Recently, there is a paradigm shift in learning from summative to formative assessment. Studies on students’ formative interaction and feedback have now gained much attention and consideration in many countries. Studies were carried out on the implementation of formative assessment for online courses in Asian countries (Chang et al., 2007; Tsai et al., 2015; Ho, 2015). The lack of f2f in an online learning environment requires universities to be innovative in creating an interactive space to support student’s learning in an online environment. As for now, there are limited studies being conducted to evaluate the online learning using formative assessment in Malaysia.